1998
DOI: 10.1136/jnnp.65.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Control of epilepsy associated with cerebral arteriovenous malformations after radiosurgery

Abstract: Objective-To investigate the eVect of radiosurgery for symptomatic epilepsy associated with cerebral arteriovenous malformations (AVMs). Methods-Thirty five patients with unruptured epileptogenic AVMs were studied with a mean follow up of 43.0 months. The duration of epilepsy before radiosurgery ranged from 2 months to 21 years (mean 2.8 years). Fifteen patients showed partial seizures; eight of these had associated secondary generalisation. The remaining 20 patients showed only generalised seizures without pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 46 publications
4
48
1
3
Order By: Relevance
“…16,33,39,57,71 In contrast, other studies have also found no significant relationship between seizure outcome and seizure type, duration, frequency, and pattern or age at seizure onset. 16,37,39,57,71 The influence of hemorrhage on seizure outcome was also controversial. Two of the 3 studies that evaluated radiosurgery margin and/or maximum dose showed no significant association between these radiosurgical parameters and seizure outcome.…”
Section: Obliteration and Other Factors Related To Seizure Outcomementioning
confidence: 84%
See 2 more Smart Citations
“…16,33,39,57,71 In contrast, other studies have also found no significant relationship between seizure outcome and seizure type, duration, frequency, and pattern or age at seizure onset. 16,37,39,57,71 The influence of hemorrhage on seizure outcome was also controversial. Two of the 3 studies that evaluated radiosurgery margin and/or maximum dose showed no significant association between these radiosurgical parameters and seizure outcome.…”
Section: Obliteration and Other Factors Related To Seizure Outcomementioning
confidence: 84%
“…For the final quantitative analysis, we identified 19 series comprising 1104 patients with AVMs and seizures who underwent SRS. 2,13,16,20,22,33,34,37,39,41,43,48,57,58,63,64,69,71,73 Figure 1 shows a flow chart of the review process.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…1,14 Rates of seizure elimination after SRS for cortical AVMs, regardless of location, range from 50% to 85%. 1,11,23,24 Seizure-free outcomes according to treatment modalities are 78% after microsurgery, 63% after radiosurgery, and 50% after embolization.…”
Section: Factors Associated With Seizuresmentioning
confidence: 99%
“…52 In contrast, our findings are in agreement with those of Kurita et al, who studied 35 patients with unruptured, epileptogenic AVMs and did not find superior seizure control in patients with obliterated AVMs. 29 Another AVM radiosurgery study of 15 pediatric patients with seizures at presentation did not find obliteration to be associated with seizure outcomes. 22 Additionally, Schauble et al reported on a series of 65 patients with AVM-associated seizures who underwent radiosurgery without a significant association between obliteration and seizure control.…”
Section: Effect Of Radiosurgery On Seizures Outcomes For Patients Witmentioning
confidence: 97%